PERAN JAMUR MIKORIZA DALAM MENINGKATKAN PERTUMBUHAN TANAMAN JAGUNG PADA LAHAN KERING UNTUK KETAHANAN PANGAN DI INDONESIA: A SYSTEMATIC LITERATURE REVIEW: dosis, jagung, jamur mikoriza, lahan kering, pertumbuhan tanaman - Marya, Desta; Ilmiasari, Yeyen (innofarm, 2025)
This article examines the role of mycorrhizal fungi in improving the growth and productivity of maize (Zea mays L.) in Indonesia's drylands, which cover an area of 1,444,732 km². The main challenge in maize cultivation in drylands is low yield due to drought and limited soil fertility. Research shows that mycorrhizal application can increase plant growth by up to 20% by improving root structure, enhancing water and nutrient uptake, and increasing resistance to drought stress. This research highlights the importance of utilizing local resources, such as organic fertilizers in combination with mycorrhiza, to improve maize yield and soil health. This combination, including the use of cow manure at varying doses, proved significant in increasing yields and reducing reliance on chemical fertilizers, thereby lowering production costs. Although the potential of mycorrhiza in sustainable agriculture is promising, there are still gaps in the understanding of its specific mechanisms. Therefore, further research is needed to determine the optimal dosage and interaction with other environmental factors, in order to support food security and agricultural sustainability amidst the challenges of climate change.